INVESTIGATION OF THYROIDS DYSFUNCTION AMONG INFERTILE WOMEN IN NASIRIYAH CITY - AMER, MUAYAD HUSSEIN; THUWAIN, MAHDI M.; AL-SNAFI, ALI E. (International Journal of Current Pharmaceutical Research, 2020)
Objective: Epidemiological studies revealed that 10-15 % of couples in the world experience infertility. Thyroid dysfunction (hyperthyroidism and hypothyroidism) possessed adverse effect on reproductive health and resulted in, interference with ovulation, reduced rates of conception, increased early pregnancy loss, and adverse effects on pregnancy and neonatal outcomes. The current study aims to explore the thyroid dysfunction among infertile women in Nasiriyah city-Iraq. Methods: The study was conducted on 60 infertile women (age group 17–45 y) who visited infertility departments in Al-Hussein hospital, Al-Haboubi hospital and Bent AL Huda hospital, in Nasiriyah city, from October 2019 to March 2020. Thirty normal females (age matched) were taken as controls. TSH, T3, T4, LH, FSH, prolactin, progesterone and estradiol levels were determine by using VIDAS® Assay. Results: The prevalence of hyperthyroidism among infertile women was 13.33% and hypothyroidism was 10.00%. Both hyper and hypothyroidism induced adverse changes in the serum levels of LH, FSH, prolactin and gonadal hormones. Conclusion: Thyroid dysfunction was associated with a risk of not getting pregnancy. Women were advised to achieve euthyroidism before planning a pregnancy.